Understanding meat consumption in later life: A segmentation of older consumers in the EU. (October 2021) - Grasso, Alessandra C.; Hung, Yung; Olthof, Margreet R.; Brouwer, Ingeborg A.; Verbeke, Wim
Highlights: Three segments of older consumers are identified using two-step cluster analysis. Segments differ in socio-demographics, appetite, protein intake, liking of protein sources. Food choice motives and food fussiness shape meat consumption behavior. Implications to sustainably meet older consumers' protein needs are discussed. Abstract: Protein intake is important for the maintenance of health, independence, and quality of life especially for older adults, yet the expanding older population is at risk of not consuming adequate levels. Notwithstanding its importance in terms of health, dietary protein choice has major ramifications for the state of the environment and for climate change, with meat holding the most weight in the environmental impact of diets. To support older consumers in making environmentally sustainable dietary protein choices, this study aims to gain deeper understanding of older consumers' meat consumption behavior by profiling older consumer segments on the basis of their meat consumption and liking. Results were obtained through a 2019-survey among 2, 500 community-dwelling older adults aged 65 years or above in Finland, Poland, Spain, the Netherlands, and the United Kingdom. Three segments of older consumers were identified by means of a two-step cluster analysis: heavy meat consumers, medium meat consumers, and light meat consumers. The segments differed significantly in several socio-demographics and background characteristics, appetite, protein intake, attitudes towards meat and plant-based 'meat' substitutes, and liking of protein sources other than meat. Health and sustainability food choice motives were important determinants for being classified as a medium or light meat consumer compared to a heavy meat consumer whereas food fussiness, sensory appeal, and familiarity were important determinants for being classified as a heavy meat consumer compared to a light meat consumer. Understanding older consumers' meat consumption behavior has important implications for designing dietary strategies to meet older consumers' protein needs in an environmentally sustainable way.